Weather protect insurance expands to 36,080 farmers in the Philippines - Swaans, Cornelis; Leyte, James Dizon; Aguila, Lea May (2024)
By December 2023, Weather Protect Insurance (WPI) — a product providing insurance coverage for climate-induced events based on trigger parameters — covered 36,080 cooperative members (7,883 women) from 103 cooperatives in 71 provinces, through Alliance-supported WPI scaling out and refinement, as well as added value through bundled training on climate-smart farming techniques and recommendations for agricultural resilience and sustainability. WPI makes meso-level payouts within ten days of the weather trigger, allowing agricultural cooperatives to manage and quickly recover from weather-related shocks.